Experiences of People Living with Parkinson's Disease in Care Homes: A Qualitative Systematic Review - Shannon Copeland; Tara Anderson; Gillian Carter; Christine Brown Wilson; Patrick Stark; Mihalis Doumas; Matthew Rodger; Emma O'Shea; Laura Creighton; Stephanie Craig; James McMahon; Arnelle Gillis; et al. (MDPI AG, 2024)
Background: Incidence of disability secondary to Parkinson's disease is increasing faster globally than any other neurological condition. The diverse appearance of symptomatology associated with Parkinson's, and the degenerative nature and subsequent functional decline, often increase dependence on caregivers for assistance with daily living, most commonly within a care home setting. Yet, primary literature and evidence synthesis surrounding these unique and complex care needs, challenges and the lived experiences of this population living in long-term nursing or residential facilities remains sparce. The aim of this review is to synthesize qualitative literature about the lived experience of people with Parkinson's disease living in care home settings. Methods: A systematic search of the literature was conducted in October 2023 across six different databases (CINAHL, Medline, EMBASE, PsycINFO, Scopus and Cochrane Library). The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was used to guide this review. Results: Five articles met the inclusion criteria. Four themes were identified following evidence synthesis: (1) Unique pharmacological challenges. (2) Transitioning and adapting to care home life and routines. (3) Dignified care within care homes. (4) Multidisciplinary care vacuum in care homes. Conclusion: This review revealed the significant and unique challenges for people with Parkinson's disease when transitioning into care homes. These are exacerbated by wider social care challenges such as staffing levels, skill mixes and attitudes as well as a lack of disease-specific knowledge surrounding symptomatology and pharmacology. The lack of multi-disciplinary working and risk-adverse practice inhibited person-centred care and autonomy and reduced the quality of life of people living with Parkinson's disease in care homes. Recommendations for practice highlight training gaps, the need for consistent and improved interdisciplinary working and better person-centred assessment and care delivery.